Performances melodramáticas QUEER: as personagens trans nos filmes de Pedro Almodóvar - Berto Júnior, Hedilberto Pessoa (2016)
Based on gender studies, media representation and Queer Theory, this research discusses the construction of identities, bodies and sexualities of trans characters in Pedro Almodovar's films, on the assumption that the filmmaker uses in his work elements that create questions about the conception of subjects, showing new ways of thinking truths about individuals, presented in his films, from slippery and fluid optical that does not hold the intelligibility standards that try to crystallize the social understanding of the bodies, identities and sexual experiences.